Comparing the accuracy of two diagnostic methods for detection of light Schistosoma haematobium infection in an elimination setting in Wolaita Zone, South Western Ethiopia. - Hussein Mohammed; Toby Landeryou; Melkie Chernet; Ewnetu Firdawek Liyew; Yonas Wulataw; Birhanu Getachew; Hailemariam Difabachew; Anna Phillips; Rosie Maddren; Alison Ower; Kalkidan Mekete; Habtamu Belay; et al. (PLoS ONE, 2022)
Reagent urinalysis dipstick and filtration have been recommended diagnostic methods for the detection of urogenital schistosomiasis. However, the accurate diagnosis of light infections using these methods presents a major challenge. This study evaluates the diagnosis accuracy of light infection with Schistosoma haematobium in study participants living in Wolaita Zone, an area targeted for sustainable control of Schistosomiasis, and ultimately interrupt transmission. Urine samples were collected from children and adults in surveys carried out during baseline and longitudinal sentinel site surveys conducted from 2018 to 2020. All urine samples were tested using a reagent urinalysis dipstick test (Haemastix) to detect microhaematuria with reference urine filtration technique as a proxy for S. haematobium infection. Sensitivity and specificity were determined in diagnosing urogenital schistosomiasis. Cohen's Kappa statistics was done for the agreement of these diagnostic methods. A total of 12,102 participants were enrolled in the current baseline study. Among them, 285 (2.35%) samples tested positive for microhaematuria and 21 (0.20%) positive for S. haematobium eggs. A total of 4,357 samples were examined in year 1 and year 2 using urine dipsticks, and urine filtration 172 (3.95%) and 2 (0.05%) were positive for microhaematuria and S. haematobium eggs. The reagent urinalysis dipsticks showed the highest sensitivity and specificity for diagnosing light intensity of infection,100% (95% CI:85.18-100.00) and 97.4% (95% CI: 97.10-97.60), respectively. There is a slight agreement between the two methods (Kappa = 0.09, 95% CI: 0.01-0.18). The present study revealed very low prevalence and light intensity of S. haematobium infections. The study also highlights that the dipstick test is considered a useful adjunct diagnostic tool for population-based control of urogenital schistosomiasis.